Intelligence and Environmental Emissions - Squalli, Jay (2014)
We hypothesize that more intelligent people are likely to forgo proximal choices for more important distal alternatives with respect to the environment, consistent with the delay discounting rationale. We undertake an assessment of the relationship between IQ and emissions of CH4, CO2, and N2O using U.S. state-level data and NAEP-derived IQ estimates for the year 2005. We find that higher-IQ U.S. states have higher N2O emissions, net of other factors. We also find no statistically significant relationship between intelligence and emissions of CH4 and CO2. While these results may suggest that higher-IQ individuals do not necessarily alter their behavior in a way that is favorable to the environment, they do not unambiguously reject the delay discounting hypothesis. Future scholarly work should consider assessing the intelligence–environment relationship using alternative measures of intelligence. It should also establish clear causality between intelligence and environmental emissions, if any, and shift research on IQ at the U.S. state level from its infancy.